Different Worlds Within Swedish Personal Social Services. Social Worker's Views on Conditions for Client Work in Different Organisational Models. - Marek Perlinski; Björn Blom; Stefan Morén (Social Work & Society, 2013)
The article presents a study of the personal social services' (PSS) organisation and economy as conditions for social workers' assessments of needs and appropriate interventions. One central aim was to study how different organisation models affect social workers' client work, especially concerning possibilities to establish supportive relationships with the clients. The study includes all staff in the PSS in three Swedish municipalities (n=247) with different organisation models: a specialised organisation, an integrated (generic) organisation as well as a combined organisation with elements of both specialisation and integration. Data collection used an on-line survey questionnaire which allowed various types of data, including relatively in-depth qualitative data. Consequently both quantitative and qualitative analysis methods were used. The results reveal significant differences between the studied organisations. Neither the specialised organisation nor the combined one is able to create sufficient economic or organisational conditions for working with clients. This also holds true for assessment of needs and possibilities to make appropriate interventions, such as establishing working alliances. Social workers in the integrated organisation, on the contrary, to a high extent report adequate conditions for assessments of needs and interventions. This organisation hence appears as more advantageous than the combined and the specialised. It is also striking that social workers in the specialised organisation perceive the organisation as not being focused on supportive relationships with clients, and sometimes as a direct obstacle. The specialised organisation is also characterised by substantial workload, social workers' lack of time for their clients and discontinuity.